Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1016/j.eurpolymj.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of polymeric powders in Laser Sintering (LS): From Polyamide to new PEEK powders

Abstract: In an attempt to expand the range of engineering polymers used for laser sintering, this paper examines the morphology, flowability and interparticle interactions of two commercially available poly (ether ether) ketone (PEEK) powders, not yet optimised for the LS process, by comparison with the LS optimised Polyamide (PA) and Polyetherketone (PEK) powdered polymers . The effect of incorporating fillers and additives on the flow behaviour is also analysed. The Particle Size Distribution (PSD) results alone do n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 33 publications
4
78
0
3
Order By: Relevance
“…The glass beads have almost perfect spherical shape, while the PEK powders have a flake like appearance. Previous particle analysis [24] of HP3 PEK powder showed that 50% volume frequency had particle size in range of 37.5-63 µm whereas the glass beads, 52% volume frequency had diameter in range of 16-27.5 µm.…”
Section: Mechanical Testingmentioning
confidence: 92%
“…The glass beads have almost perfect spherical shape, while the PEK powders have a flake like appearance. Previous particle analysis [24] of HP3 PEK powder showed that 50% volume frequency had particle size in range of 37.5-63 µm whereas the glass beads, 52% volume frequency had diameter in range of 16-27.5 µm.…”
Section: Mechanical Testingmentioning
confidence: 92%
“…Highly circular and round particles with smooth surfaces and fully dense structure were found to achieve higher flow behaviour. In a previous publication the authors showed that [5] particles with smoother surfaces, rounder and circular shapes exhibited a better flow behaviour. Circularity is a shape descriptor that quantifies how much a given particle shape is similar to a circle overall, roundness is instead a shape descriptor that indicates how round the edges of a particle are.…”
Section: Particle Morphologymentioning
confidence: 95%
“…Berretta et al [5] quantitatively analysed size and morphological characteristics of new potential candidate HT polymers and their composites in parallel with established Laser Sintering (LS) materials such as PEK HP3 and PA 2200. The study highlighted that a simple particle size analysis is not sufficient when searching for new HT-LS powder candidates.…”
Section: Particle Morphologymentioning
confidence: 99%
See 2 more Smart Citations